Alg2-Chap2-Linear Mappings
Alg2-Chap2-Linear Mappings
bachelor’s degree.
Chapter 2: Linear Mappings
February 2024
Examples
1 The Identity mapping (id : A → A; id (u ) = u ) is linear.
2 The Zero mapping (O : A → B; O (u ) = 0B ) is linear.
3 The Projection mappings
exmpl : f : R3 → R2 ; f (x, y , z ) = (y , z ) .
f (αu + βv ) = αf (u ) + βf (v ) .
Example
Let f : R2 → R2 such that f (x, y ) = (x + y , x − y ) . Taking two vectors
u = (a, b ) and v = (a0 , b 0 ) and two scalars α, β ∈ R, we have
f (αu + βv ) = f αa + βa0 , αb + βb 0
αa + βa0 + αb + βb 0 , αa + βa0 − αb + βb 0
=
= (αa + αb, αa − αb ) + βa0 + βb 0 , βa0 − βb 0
= αf (a, b ) + βf a0 , b 0 = αf (u ) + βf (v ) .
Dr. Louiza TABHARIT FSEI. Univ-Mosta February 2024 3 / 17
Linear Form
Definition
A linear form ( or one-form) is a linear mapping from a vector space to
its field of scalars(i.e. f : A → IF ) .
The set of all linear forms is denoted by L (A, IF ) .
Exemple
1 f : R2 → R; f (x, y ) = x + y .
2 g : R3 → R; g (x, y , z ) = 4 (x + 2y − z ) .
Remark
the mapping f : R → R; f (x ) = x + a with a ∈ R∗ is not linear (but is
an affine transformation).
Proof.
for (1) use α = 0 and for (2) use α = −1.
Proposition
Let f : A → B be a Linear mapping and {u1 , · · · , un } a spanning set of A,
we have
n n
∀v ∈ A, ∃ (α1 , · · · , αn ) ∈ IF n : v = ∑ αi ui =⇒ f (v ) = ∑ α i f ( ui )
i =1 i =1
Proof.
Let α, β ∈ IF , and two images a, b ∈ B. Since f is a bijective,
∃!u ∈ A : f (u ) = a, and ∃!v ∈ A : f (v ) = b. So,
f −1 (αa + βb ) = f −1 (αf (u ) + βf (v ))
= f −1 (f (αu ) + f ( βv ))
= f −1 (f (αu + βv ))
= αu + βv
= αf −1 (a) + βf −1 (b ) .
Proof.
Let α, β ∈ IF ; u, v ∈ A :
(g ◦ f ) (αu + βv ) = g (f (αu + βv ))
= g (αf (u ) + βf (v ))
= g (αf (u )) + g ( βf (v ))
= αg (f (u )) + βg (f (v ))
= α (g ◦ f ) (u ) + β (g ◦ f ) (v ) .
ker f = {u ∈ A : f (u ) = 0B } = f −1 ({0B }) .
Example
Let f : R2 → R2 ; f (x, y ) = (x + y , x − 3y ) .
u ∈ R 2 : f ( u ) = 0 R2
ker f =
= (x, y ) ∈ R2 : f (x, y ) = (0, 0)
= (x, y ) ∈ R2 : (x + y , x − 3y ) = (0, 0)
Example
Let g : R3 → R2 ; g (x, y , z ) = (x + y + z, −x + 2y + 2z )
u ∈ R3 : f (u ) = 0R2
ker g =
= (x, y , z ) ∈ R3 : f (x, y , z ) = (0, 0)
= (x, y , z ) ∈ R3 : x + y + z = 0 ∧ −x + 2y + 2z = 0
= (x, y , z ) ∈ R3 : y = −z ∧ x = 0
= {(0, −z, z ) /z ∈ R}
= {z (0, −1, 1) /z ∈ R}
ker g = span {a} /a = (0, −1, 1) .
Proof.
(⇐) Suppose that f is injective. So, we have
f Lin f inj
u ∈ ker f =⇒ f (u ) = 0B = f (0A ) =⇒ u = 0A .
(⇒) Suppose that ker f = {0A } . To prove that f is injective we take
u, v ∈ A, such that
f (u ) = f (v ) =⇒ f (u ) − f (v ) = 0B =⇒ f (u − v ) = 0B
=⇒ u − v ∈ ker f =⇒ u − v = 0A =⇒ u = v .
So, f is injective.
Dr. Louiza TABHARIT FSEI. Univ-Mosta February 2024 10 / 17
Image of a linear mapping
Definition
Let f : A → B be a linear mapping. The Image of f is the set :
Imf = f (A) = {f (u ) ∈ B : u ∈ A} .
Example
Let f : R2 → R2 ; f (x, y ) = (x + y , x − 3y ) .
Imf = {f (u ) ∈ B : u ∈ A}
(x + y , x − 3y ) ∈ R2 : (x, y ) ∈ R2
=
= {(x, x ) + (y , −3y ) : x, y ∈ R}
= {x (1, 1) + y (1, −3) : x, y ∈ R}
= span {c, d } /c = (1, 1) and d = (1, −3) .
Example
Let g : R3 → R2 ; g (x, y , z ) = (x + y + z, −x + 2y + 2z ) :
Img = {g (u ) ∈ B : u ∈ A}
(x + y + z, −x + 2y + 2z ) ∈ R2 : (x, y , z ) ∈ R3
=
= {(x, −x ) + (y , 2y ) + (z, 2z ) : x, y , z ∈ R}
= {x (1, −1) + [y + z ] (1, 2) : x, y , z ∈ R}
= span {c, d } /c = (1, −1) and d = (1, 2) .
Proposition
Let f : A → B be a linear mapping.
Prop1: Imf is a subspace of the vector space B.
Prop2: Imf = B ⇔ f is surjective.
Proof.
f is surjective ⇔ ∀v ∈ B, ∃u ∈ A : v = f (u ) . Witch means that v ∈ Imf .
Hence, B ⊆ Imf . And, we know that Imf ⊆ B. Then, Imf = B.
Proposition
Let f : A → B be a linear mapping and let E be a subset of independent
vectors from A and F a spanning set of A.
1 f is injective⇔ The vectors of f (E ) are independent.
2 f is surjective⇔ f (F ) is a spanning set of B.
Corollary
Let f : A → B be a linear mapping and G is a basis of A :
f is bijective ⇔ f (G ) is a basis of B
Proposition
Let f : A → B be a linear mapping and let E = {u1 , · · · , un } be a subset
of A.
1 E is L. dependent =⇒ f (E ) is L. dependent.
2 f (E ) is L. independent =⇒ E is L. independent.
Proof.
(Prop1): If E is L. dependent then ∃ (α1 , · · · , αn ) ∈ IF n − {(0, · · · , 0)}
n
such that ∑ αi ui = 0A . So,
i=
1
n n
f ∑ αi ui = f (0A ) =⇒ ∑ αi f (ui ) = 0B . Thus, f (ui ) are L.
i =1 i =1
dependent.
(Prop2): is the contrapositive of the proposition 1.
Corollary
Let f : A → B be a linear mapping, the following holds:
1 f injective =⇒ dim (A) ≤ dim (B ) ;
2 f surjective =⇒ dim (A) ≥ dim (B ) ;
3 f bijective =⇒ dim (A) = dim (B ) .
Remark
The converse implications are not necessarily true.
Dr. Louiza TABHARIT FSEI. Univ-Mosta February 2024 17 / 17